Cyclopeptidic photosensitizer prodrugs as proteolytically triggered drug delivery systems of pheophorbide A: part II – co-loading of pheophorbide A and black hole quencher. Issue 11 (14th September 2018) - Bouilloux, Jordan; Yuschenko, Oleksandr; Dereka, Bogdan; Boso, Gianluca; Babič, Andréj; Zbinden, Hugo; Vauthey, Eric; Lange, Norbert
Abstract : Co-loading of pheophorbide A and black hole quencher moieties onto cyclopeptidic templates led to photosensitizer prodrugs with ultra-high initial quenching. Abstract : Previously, we have shown that the use of a cyclopeptidic carrier could be of great interest for the design of fully characterized prodrugs for further use in photodynamic therapy. In order to further optimize the design, we decided to modify the highly quenched conjugate uPA-cPPP4/5 by co-loading a long-distance fluorescence quencher. For this purpose we tethered two black hole quenchers (BHQ3) together with two pheophorbide A moities onto the same PEGylated backbone and assessed the modified photophysical properties. In addition, to prove the reliability of our concept, we designed two analogues, uPA-cPPQ2+2/5 and CathB-cPPQ2+2/5, by using two different peptidic linkers as substrates for uPA and cathepsin B, respectively. These two conjugates proved to be much more water-soluble than their analogues bearing only Phas. These conjugates are not only highly quenched in their native state with regard to their fluorescence emission (up to 850 ± 287 times less fluorescent for CathB-cPPQ2+2/5 as compared to the unquenched monosubstituted reference uPA-cPPP1/5 ), but also prevent singlet oxygen production (with a total quenching of the emission when the quenchers are co-loaded with photosensitizers) when the photosentistizers are excited. After proteolytic activation, these conjugates recover their photophysical properties in the same way as occurred for uPA-cPPP4/5, with up to a 120-fold increase in fluorescence emission for uPA-cPPQ2+2/5 after two hours of incubation with uPA.